Rapid analysis of shipworm attack - a novel digital tool for assessing shipworm damage (RANDA) - Anne Marie Høier Eriksen; Malte Skov Jepsen; Carsten Gundlach; David John Gregory; Arne Redsted Rasmussen; Henning Matthiesen (Results in Engineering)
Shipworm (Teredo navalis) poses a significant threat to wooden structures and archaeological artifacts in marine environments, leading to extensive biodeterioration. Quantifying shipworm damage remains challenging due to the limitations of traditional assessment methods, which are often invasive, time-consuming, and/or subjective. In this study, we introduce RANDA (Rapid Analysis Digital Tool), a software designed to assess shipworm damage severity through image-based analysis of entry holes on wood surfaces, with the potential for non-destructive application. Data from 232 T. navalis entry holes and tunnels revealed a strong correlation between entry hole size and tunnel volume, suggesting that surface analysis can approximate internal damage. When applied to eight test panels, RANDA degradation estimates differed by -0.69±1.05 % from weight loss analysis and by 2.74 ± 1.67 % from tunnel volume measurements obtained via CT imaging. For hole classification, the RANDA model achieved a precision of 80 % and a recall of 81 %. While currently validated under controlled conditions, this method offers a rapid and reliable alternative to conventional approaches and represents an important step toward a non-destructive in situ assessment tool.